The Report of Lightning in Himalayan Locale - Pitri Bhakta Adhikari (The Scientific World Journal)
A few normal calamities (disasters) as often as possible happen within the Himalayan locale in Nepal. The height of this locale ranges from 59 m to “8848.86 m” along the range of 160 km. As a result, there is a significant variety of temperatures within the locale. In addition, Nepal includes a heterogeneous geography. All these highlights impact different normal fiascos counting the lightning action. This report points at analyzing the varieties of lightning inside and over a long time from January 2011 to present. For this report, the information was taken from the Disaster Risk Reduction (DRR) portal of the Ministry of Home Affairs (MOHA). The investigation indicated that there was no lightning occasion in November, and the lightning stroke density was higher in the premonsoon period, and the number of harmed individuals was almost three times the number of individuals passing due to the lightning.